1403PEfficacy of immune check-point inhibitors (ICPi) in large cell neuroendocrine tumours of lung (LCNET). (1st October 2019) - Sherman, S; Rotem, O; Zer, A; Shochat, T; Dudnik, E
Abstract: Background: Little is known regarding the efficacy of ICPi in LCNET. Methods: Thirty seven consecutive patients (pts) with advanced LCNET were selected from the Davidoff Cancer Center database. These were divided into Groups A1 (pts treated with ICPi, n-23) and A2 (pts not treated with ICPi, n-14). Another cohort of advanced non-small cell lung cancer (NSCLC) pts treated with nivolumab at five Israeli cancer centers in 2015-2016 was chosen as a comparator (Group B, n-270). ORR, PFS with ICPi in Group A1 were assessed (RECIST 1.1), OS with ICPi was compared between Groups A1 and B. OS since advanced disease diagnosis (OSDx) was compared between Groups A1 and A2. Results: Baseline pts characteristics are presented in the table. In Group A1* (n-21, 2 pts receiving combined ICPi + chemotherapy were excluded), ORR and median PFS with ICPi were 33%, and 4.2 months (95% CI, 2.4-8.1), respectively. With median follow-up since start of ICPi of 6.2 months [IQR 2.2-12.1] and 4.9 months [IQR 2.3-8.9] in Groups A1* and B, respectively, 52% of pts in Group A1* and 64% of pts in Group B had died. Median OS with ICPi comprised 11.8 months (95% CI, 3.7-NR) and 6.9 months (95% CI, 5.5-8.1) in Groups A1* and B, respectively (p-0.23). Median OSDx was 14.5 months (95% CI, 10.1-38.9) and 10.3 months (95% CI, 2.6-NR), in Groups A1 and A2, respectively (p-0.54). Abbreviations: Tx- treatment, N – nivolumab, P-pembrolizumab, A- atezolizumab. Conclusions: In advanced LCNET, ICPi outcomes are comparable to the outcomes observed in advanced NSCLC. Future prospective research is needed to clarify the impact of ICPi on OS in LCNET. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: A. Zer: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: AstraZeneca, Roche, BMS, MSD, BI, TAKADA. E. Dudnik: Research grant / Funding (self): Roche, Boehringer Ingelheim; Advisory / Consultancy: Boehringer Ingelheim, Roche, AstraZeneca, Pfizer, MSD, BMS, Novartis, Takeda. All other authors have declared no conflicts of interest.